Accountability and revenue metering in smart micro-grids - Tenti, Paolo; Morales Paredes, Helmo K.; Marafão, Fernando P. [UNESP]; Mattavelli, Paolo (Institute of Electrical and Electronics Engineers (IEEE), 2010)
Smart micro-grids offer a new challenging domain for power theories and metering techniques, because they include a variety of intermittent power sources which positively impact on power flow and distribution losses, but may cause voltage asymmetry and frequency variation. Due to the limited power capability of smart micro-grids, the voltage distortion can also get worse (in case of supplying non-linear loads), affecting measurement accuracy and possibly causing tripping of protections. In such a context, a reconsideration of power theories is required, since they form the basis for supply and load characterization. A revision of revenue metering techniques is also needed, to ensure a correct penalization of the loads for their responsibility in generating reactive power, voltage unbalance and distortion. This paper shows that the Conservative Power Theory (CPT) provides a suitable background to cope with smart grids characterization and metering needs. Experimental results validate the proposed approach. © 2010 IEEE.
Keywords: Accountability; Microgrid; Power measurement; Revenue metering; Smart grid; Micro grid